2011
DOI: 10.1021/ja206873f
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of cis-3-Chloroacrylic Acid Dehalogenase with an Allene Substrate, 2,3-Butadienoate: Hydration via an Enamine

Abstract: cis -3-Chloroacrylic acid dehalogenase (cis-CaaD) catalyzes the hydrolytic dehalogenation of cis-3-haloacrylates to yield malonate semialdehyde. The enzyme processes other substrates including an allene (2,3-butadienoate) to produce acetoacetate. In the course of a stereochemical analysis of the cis-CaaD-catalyzed reaction using this allene, the enzyme was unexpectedly inactivated in the presence of NaBH4 by the reduction of a covalent enzyme-substrate bond. Covalent modification was surprising because the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(88 citation statements)
references
References 48 publications
(147 reference statements)
4
84
0
Order By: Relevance
“…The chemical shifts for 4, 5, their hydrates, 11, and 12 are reported elsewhere. 13,21 The approximate amount of product in the mixtures was determined by integration, as described previously. 1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical shifts for 4, 5, their hydrates, 11, and 12 are reported elsewhere. 13,21 The approximate amount of product in the mixtures was determined by integration, as described previously. 1 …”
Section: Methodsmentioning
confidence: 99%
“…3,21 After a 48-h incubation period, the resulting peptide mixture was analyzed by MALDI- MS, as described previously. 3,21 …”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, it was anticipated that Cg10062 would function as a cis-CaaD with the same mechanism and activity even though there did not appear to be a catabolic pathway for 1 in C. glutamicum (based on the genomic context). However, a comparison of the kinetic parameters for cis-CaaD and Cg10062 showed that 2 is a poor substrate for Cg10062 due to a high value of K m (72,000 vs 200 μM) resulting in an overall k cat /K m of 14 M À 1 s À 1 (1570-fold lower than that measured for cis-CaaD) (Poelarends et al, 2008a;Schroeder et al, 2012Schroeder et al, , 2013. In addition, Cg10062 processed the trans isomer, albeit poorly (0.8 M À 1 s À 1 using 3) (Poelarends et al, 2008a).…”
Section: Characterization Of Cg10062mentioning
confidence: 95%
“…cis-CaaD functions as a hydratase using 2, 11 (k cat / K m $6.4 Â 10 3 M À 1 s À 1 , as noted above), and 12 (k cat / K m $8.7 Â 10 3 M À 1 s À 1 ) (Schroeder et al, 2012). cis-CaaD processes 14 to 13, (determined by 1 H NMR spectroscopy), but the rate is too slow to obtain kinetic parameters.…”
Section: Deciphering the Reaction Mechanism Of Cg10062mentioning
confidence: 99%
“…3). 10 As part of our ongoing research programs of allenes, 11 herein, we report a general and efficient …”
Section: Introductionmentioning
confidence: 99%